Supercritical Fluid Electrodeposition of Elemental Germanium onto Titanium Nitride Substrates. Issue 14 (1st January 2015) - Cummings, Charlie Y.; Bartlett, Philip N.; Pugh, David; Reid, Gillian; Levason, William; Hasan, Mahboba M.; Hector, Andrew L.; Spencer, Joe; Smith, David C.
Abstract : We report the electrodeposition of germanium from supercritical difluoromethane (sc-CH2 F2 ) at 19 MPa and 358 K using [N n Bu4 ][GeCl3 ]. Voltammetry shows a classic nucleation loop on the first anodic scan with a high nucleation overpotential for germanium on TiN. In all cases the deposition appears to be kinetically limited by a coupled, potential independent, chemical step. Films of germanium were deposited at a range of potentials. At high overpotentials the films were dendritic and poorly adherent. At lower overpotentials, below −2 V vs. Ag|LaF3, the films are smoother and more homogeneous. Analysis of the films by energy dispersive X-ray (EDX) spectroscopy shows the presence of germanium with some chloride impurity. Raman spectroscopy confirms the deposition of amorphous germanium. Plating by pulsing to −1.9 V vs. Ag|LaF3 for 100 ms and then growth at −1.5 V vs. Ag|LaF3, was found to produce the best films. On annealing at 700°C under an Ar atmosphere for 1 hour the as-deposited amorphous germanium film is converted into crystalline germanium, as determined by X-ray diffraction (XRD) and Raman spectroscopy.